WAYS TO ENSURE FINANCIAL STABILITY OF INSURANCE COMPANIES IN UZBEKISTAN - Juraev Dilshod Maxmudjonovich (American Journals, 2024)
The relevance of this study lies in the fact that, based on the analysis of modern trends in the insurance system, reasons for the underdevelopment of the insurance market in Uzbekistan to date have been determined. The article shows the need of relationship between state regulation and self-regulation and the role of creation of formal institutions and the institutional environment for development of the insurance market in Uzbekistan. According to the conclusions drown, proposals to solve problems and develop the insurance market have been made. Formation and development of the market economy fundamentally changes the role and place of insurance in the system of economic relations. Insurance companies become one of the most important institutions of the modern national economy and play an important role in ensuring its continuous and efficient operation and sustainable growth., based on the imperfection of formal and informal institutions in our republic.
Keywords: Insurance, insurance functions, insurance institution, official institutions, insurance premium, insurance market, insurance coverage, risk, risk distribution